Метод интерпретации данных огневых испытаний железобетонных колонн для расчетной оценки их огнестойкости - Pozdeev Сергей; Slovinskiy Виталий; Shchipets Станислав; Omel’chenko Андрей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2014)
In the article the questions of realization of experimental-calculation method of estimation of fire-resistance of reinforced concrete columns on the basis of their fire tests without the appendix of the mechanical loading are considered. This method is used for estimation of limit of fire-resistance of reinforced concrete column, his high exactness and authenticity is shown as a result.